Provably secure and efficient certificateless sequential multi-signature scheme in random oracle model - Yan XU; Liu-sheng HUANG; Miao-miao TIAN; Hong ZHONG (Tongxin xuebao)
Certificate less sequential multi-signature scheme could resolve the problem of authentication of recommendation information transmitted through trust train.Qin yan-lin，et al proposed an efficient certificateless sequential multi-signature scheme，and proved the security is based on the fact that computational Diffie-Hellman problem is hard in the random oracle.It is found that Qin's scheme is insecure against the forgery attack after analysing the security proof.If an adversary has obtained the signers’ multi-signature，it can forgery the multi-signature for any other message.Then，a more efficient certificateless sequential multi-signature scheme is construced which has lower computation cost and communication cost for using less bilinear pairings and only generating one signature message.Finally，the security proof shows that the proposed scheme can resist the forgery attack under the model of random oracle.